Incidence of seroma and postoperative complications after breast surgery before and during the Covid-19 pandemic: results from a retrospective multicenter analysis - Maximilian Heinz Beck; Izabela A. Brachaczek; Pimrapat Gebert; Jens-Uwe Blohmer; Askin C. Kaya; Julia S. M. Zimmermann; Julia C. Radosa; Maria M. Karsten (BMC Cancer)
Abstract Background In recent years, there has been a growing number of case reports documenting delayed seroma in patients with a history of breast surgery and reconstruction. The occurrence of these seromas has been associated with prior SARS-CoV-2 infection or SARS-CoV-2 vaccination. So far, there are few systematic analyses on postoperative complications in breast surgery since the emergence of the SARS-CoV-2 pandemic. Study design We conducted a multicenter retrospective analysis to assess the incidence of postoperative complications in two major university breast care centers in Germany during the SARS-CoV-2 pandemic (August 1st, 2021, to January 31st, 2022) compared to a reference period (August 1st, 2019, to January 31st, 2020) before the pandemic. Results A total of 987 patients were included in this retrospective analysis, with 492 patients during the SARS-CoV-2 pandemic and 495 patients in the reference period. There was no significant difference in the incidence rate of seroma after breast surgery. However, complications such as erythema, wound infection, and wound healing disorders were notably more frequent during the SARS-CoV-2 pandemic. Multivariate analysis revealed that increasing patient age, smoking, breast implant reconstruction, axillary lymph node dissection, and previous radiation were significant clinical risk factors for seroma development. Conclusion While our findings did not indicate an elevated incidence of seroma during the SARS-CoV-2 pandemic, we observed increased rates of erythema, wound healing disorders, and wound infection. Additional real-world evidence is needed for understanding both early and late complications following breast surgery in the context of the ongoing SARS-CoV-2 endemic.